Application of geographical information systems to assess the risk of trypanosomosis in Apete, Ibadan (2001)
Geography information System (GIS) was applied to assess the risk of trypanosomosis at Apete area, Ibadan, Nigeria where the University of Ibadan’s Veterinary Teaching Hospital has a satellite station. Primary data were collected from physical field observations and interviews with residents and community leaders in the area between September 2000 and March 200.1 Secondary data sources included maps from Oyo State ministry of Land, Housing and Survey, International Livestock Research Institute ILRI. Internet Search and consultation with GIS personnel at the Geography Department of the University of Ibadan. Data analysis was done at DISEG Niq Ltd Ibadan. Software used included Arcview GIS Version 3.1® Atlas GIS® and Arc info GIS Microsoft Word 98® was used for typing Epizootological criteria chosen included the Forest Reserve Area Rivers and An-mal Host locations at Apete area. Results classified Apete area into high risk and medium risk areas and highlight the potential of GIS for landscape epizootological research. Recommendation are made for provision of relevant database of high quality which should be regularly updated. There is need for collaborative efforts with the GIS unit of Geography Department of the University.